The american continent in fundamental teaching: a methodological proposal from the stage supervised in geography - Brito, Dayane Galdino; Melo, Josandra Araújo Barreto de (Geosaberes; Vol 8 No 15 (2017): May - Aug, 2017)
This work analyzes the educational project developed under the Supervised Internship in Geography, of the Geography Course of the Universidade Estadual da Paraíba, in a group of the 8th year of Basic Education in a public school in the Boqueirão-PB town, in which the American continent was approached from different strategies and didactic resources. It aimed to promote a critical analysis of America, from the elements that permeated its spatial production process and the consequences of this in its current organization. From the activities, in addition to the interest that was aroused, the students understood that the differences existing between Latin America and Anglo-Saxon America, result from the way in which they have been inserted in the International Division of  Labor, since the colonization, demonstrating that Geography can contribute to a critical and reflective formation.
Keywords: Ensino de Geografia; Estágio; América; Recursos didáticos